High-throughput metabolomic and transcriptomic analyses vet the potential route of cerpegin biosynthesis in two varieties of Ceropegia bulbosa Roxb. - Gharat, Sachin A.; Shinde, Balkrishna A.; Mule, Ravindra D.; Punekar, Sachin A.; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Ramaswamy, Gopalakrishna; Giri, Ashok P. (Planta, 2020)
Ceropegia bulbosa is an important medicinal plant, used in the treatment of various ailments including diarrhea, dysentery, and syphilis. This is primarily attributed to the presence of pharmaceutically active secondary metabolites, especially cerpegin. As this plant belongs to an endemic threatened category, genomic resources are not available hampering exploration on the molecular basis of cerpegin accumulation till now. Therefore, we undertook high-throughput metabolomic and transcriptomic analyses using different tissues from two varieties namely, C. bulbosa var. bulbosa and C. bulbosa var. lushii. Metabolomic analysis revealed spatial and differential accumulation of various metabolites. We chemically synthesized and characterized the cerpegin and its derivatives by liquid chromatography tandem-mass spectrometry (LC-MS/MS). Importantly, these comparisons suggested the presence of cerpegin and 5-allyl cerpegin in all C. bulbosa tissues. Further, de novo transcriptome analysis indicated the presence of significant transcripts for secondary metabolic pathways through the Kyoto encyclopedia of genes and genomes database. Tissue-specific profiling of transcripts and metabolites showed a significant correlation, suggesting the intricate mechanism of cerpegin biosynthesis. The expression of potential candidate genes from the proposed cerpegin biosynthetic pathway was further validated by qRT-PCR and NanoString nCounter. Overall, our findings propose a potential route of cerpegin biosynthesis. Identified transcripts and metabolites have built a foundation as new molecular resources that could facilitate future research on biosynthesis, regulation, and engineering of cerpegin or other important metabolites in such non-model plants.
Keywords: 5-Allyl cerpegin; Ceropegia; Cerpegin; LC-MS; metabolite; Transcriptome

2-oxoglutarate-dependent dioxygenases drive expansion of steroidal alkaloid structural diversity in the genus Solanum - Sonawane, Prashant D.; Jozawiak, Adam; Barbole, Ranjit; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Gharat, Sachin A.; Ramot, Ofir; Unger, Tamar; Wizler, Guy; Meir, Sagit; Rogachev, Ilana; et al. (New Phytologist, 2022)
Solanum steroidal glycoalkaloids (SGAs) are renowned defence metabolites exhibiting spectacular structural diversity. Genes and enzymes generating the SGA precursor pathway, SGA scaffold and glycosylated forms have been largely identified. Yet, the majority of downstream metabolic steps creating the vast repertoire of SGAs remain untapped. Here, we discovered that members of the 2-OXOGLUTARATE-DEPENDENT DIOXYGENASE (2-ODD) family play a prominent role in SGA metabolism, carrying out three distinct backbone-modifying oxidative steps in addition to the three formerly reported pathway reactions. The GLYCOALKALOID METABOLISM34 (GAME34) enzyme catalyses the conversion of core SGAs to habrochaitosides in wild tomato S. habrochaites. Cultivated tomato plants overexpressing GAME34 ectopically accumulate habrochaitosides. These habrochaitoside enriched plants extracts potently inhibit Puccinia spp. spore germination, a significant Solanaceae crops fungal pathogen. Another 2-ODD enzyme, GAME33, acts as a desaturase (via hydroxylation and E/F ring rearrangement) forming unique, yet unreported SGAs. Conversion of bitter alpha-tomatine to ripe fruit, nonbitter SGAs (e.g. esculeoside A) requires two hydroxylations; while the known GAME31 2-ODD enzyme catalyses hydroxytomatine formation, we find that GAME40 catalyses the penultimate step in the pathway and generates acetoxy-hydroxytomatine towards esculeosides accumulation. Our results highlight the significant contribution of 2-ODD enzymes to the remarkable structural diversity found in plant steroidal specialized metabolism.
Keywords: Solanum; specialized metabolism; steroidal glycoalkaloids (SGAs); structural diversity; Tomato

BAHD-type acyltransferase concludes the biosynthetic pathway of non-bitter glycoalkaloids in ripe tomato fruit - Sonawane, Prashant D.; Gharat, Sachin A.; Jozwiak, Adam; Barbole, Ranjit; Heinicke, Sarah; Almekias-Siegl, Efrat; Meir, Sagit; Rogachev, Ilana; O'Connor, Sarah E.; Giri, Ashok P.; Aharoni, Asaph (Nature Communications, 2023)
During tomato fruit ripening, bitter and toxic steroidal glycoalkaloids (SGAs) are converted to nonbitter and less toxic forms, but proposed acylating enzyme in pathway remain unknown. Here, authors report BAHD-type acyltransferase that catalyze acylation step in biosynthesis of non-bitter SGAs in tomato. Tomato is the highest value fruit and vegetable crop worldwide, yet produces & alpha;-tomatine, a renowned toxic and bitter-tasting anti-nutritional steroidal glycoalkaloid (SGA) involved in plant defense. A suite of modifications during tomato fruit maturation and ripening converts & alpha;-tomatine to the non-bitter and less toxic Esculeoside A. This important metabolic shift prevents bitterness and toxicity in ripe tomato fruit. While the enzymes catalyzing glycosylation and hydroxylation reactions in the Esculeoside A pathway have been resolved, the proposed acetylating step remains, to date, elusive. Here, we discovered that GAME36 (GLYCOALKALOID METABOLISM36), a BAHD-type acyltransferase catalyzes SGA-acetylation in cultivated and wild tomatoes. This finding completes the elucidation of the core Esculeoside A biosynthetic pathway in ripe tomato, allowing reconstitution of Esculeoside A production in heterologous microbial and plant hosts. The involvement of GAME36 in bitter SGA detoxification pathway points to a key role in the evolution of sweet-tasting tomato as well as in the domestication and breeding of modern cultivated tomato fruit.

Navigating the challenges of engineering composite specialized metabolite pathways in plants - Gharat, Sachin A.; Tamhane, Vaijayanti A.; Giri, Ashok P.; Aharoni, Asaph (Plant Journal, 2025)
Plants are a valuable source of diverse specialized metabolites with numerous applications. However, these compounds are often produced in limited quantities, particularly under unfavorable ecological conditions. To achieve sufficient levels of target metabolites, alternative strategies such as pathway engineering in heterologous systems like microbes (e.g., bacteria and fungi) or cell-free systems can be employed. Another approach is plant engineering, which aims to either enhance the native production in the original plant or reconstruct the target pathway in a model plant system. Although increasing metabolite production in the native plant is a promising strategy, these source plants are often exotic and pose significant challenges for genetic manipulation. Effective pathway engineering requires comprehensive prior knowledge of the genes and enzymes involved, as well as the precursor, intermediate, branching, and final metabolites. Thus, a thorough elucidation of the biosynthetic pathway is closely linked to successful metabolic engineering in host or model systems. In this review, we highlight recent advances in strategies for biosynthetic pathway elucidation and metabolic engineering. We focus on efforts to engineer complex, multi-step pathways that require the expression of at least eight genes for transient and three genes for stable transformation. Reports on the engineering of complex pathways in stably transformed plants remain relatively scarce. We discuss the major hurdles in pathway elucidation and strategies for overcoming them, followed by an overview of achievements, challenges, and solutions in pathway reconstitution through metabolic engineering. Recent advances including computer-based predictions offer valuable platforms for the sustainable production of specialized metabolites in plants.
Keywords: Biosynthetic pathway; Enzyme activity; Gene expression; Metabolic engineering; Metabolites